DENV-3 precursor membrane (prM) glycoprotein enhances E protein immunogenicity and confers protection against DENV-2 infections in a murine model - Roberto S. Dias; Michelle D. Teixeira; Mariana F. Xisto; John W. O. Prates; Jessica D. Da Silva; Iago O. Mello; Cynthia C. Da Silva; Sérgio O. De Paula (Taylor & Francis Group, 2021)
To improve a DNA vaccine containing the truncated dengue virus serotype 2 (DENV-2) envelope (E) protein and evaluate the influence of precursor membrane (prM) glycoprotein polymorphism on E protein immunogenicity, two vaccine candidates have been constructed by upstream insertion of the DENV-2 and DENV-3 prM genes into the DENV-2 E gene, named pCID2EtD2prM and pCID2EtD3prM, respectively. Both constructs were able to induce antibody production, which were neutralizing against DENV-2 in a murine model. Splenocytes of immunized groups, when challenged with virus, demonstrated Th1 cytokine pattern and proliferation, in addition to the increase of specific T cells. Vaccine candidates pCID2EtD2prM and pCID2EtD3prM confer 70% and 90% protection against DENV-2, respectively. The pCID2EtD3prM plasmid conferred only 40% protection in the lethal challenge with DENV-2. The results demonstrate that DENV-3 prM has a greater influence on the immunogenicity of the E protein and, probably due to its role as a chaperone, these results may be related to the correct folding and, consequently, an increase in the presentation efficiency of produced transcripts.